Significance of Hall effect and Ion slip in a three-dimensional bioconvective Tangent hyperbolic nanofluid flow subject to Arrhenius activation energy - Ramzan, Muhammad; Gul, Hina; Chung, Jae Dong; Kadry, Seifedine; Chu, Yu-Ming (Scientific reports, 2020)
The dynamics of partially ionized fluid flow subjected to the magnetic field are altogether distinct in comparison to the flow of natural fluids. Fewer studies are available in the literature discussing the alluring characteristics of the Hall effect and the Ion slip in nanofluid flows. Nevertheless, the flow of nanofluid flow with Hall and Ion slip effect integrated with activation energy, gyrotactic microorganisms, and Cattaneo–Christov heat flux is still scarce. To fill in this gap, our aim here is to examine the three dimensional electrically conducting Tangent hyperbolic bioconvective nanofluid flow with Hall and Ion slip under the influence of magnetic field and heat transmission phenomenon past a stretching sheet. Impacts of Cattaneo–Christov heat flux, Arrhenius activation energy, and chemical reaction are also considered here. For the conversion of a non-linear system to an ordinary one, pertinent transformations procedure is implemented. By using the bvp4c MATLAB function, these equations with the boundary conditions are worked out numerically. The significant impacts of prominent parameters on velocity, temperature, and concentration profiles are investigated through graphical illustrations. The results show that the velocity of the fluid is enhanced once the Ion slip and Hall parameters values are improved. Furthermore, the concentration is improved when the values of the activation energy parameter are enhanced.